Moving Target Tracking of Extended Nonholonomic Chained-Form Systems via Finite-Time Switching Control - Hua Chen; Lei Chen; Fei Tong (Discrete Dynamics in Nature and Society)
A finite-time switching control scheme is presented for tracking a practical moving target of extended nonholonomic chained-form systems. Firstly, a dynamic output tracking error model is proposed combining moving target and extended nonholonomic chained-form systems. Secondly, two decoupled subsystems are considered for the tracking error systems, based on which the rigorous convergence and stability analysis are proposed by applying the finite-time stability control theory and switching design methods. Finally, the effectiveness of the proposed finite-time switching control approach is performed according to the further simulation results.